2014
DOI: 10.1177/0022022114542283
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Differences in Parenting Styles of Mother–Daughter Dyads Among Immigrants and Native-Born Israelis

Abstract: The study examined and compared intergenerational differences in parenting styles, attitudes toward child-rearing, and corporal punishment (CP) in three groups of mother–daughter dyads in Israel: immigrants from Ethiopia and from the Former Soviet Union (FSU) and native-born Israelis. Results show that ethnicity, mothers’ parenting styles, and mothers’ attitudes toward CP significantly explain 21% to 26% of the variance in daughters’ parenting styles. However, the results also indicate the differential effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…It includes 62 items divided into 3 scales: authoritative parenting style, authoritarian parenting style, and permissive parenting style. Good internal consistencies were found (Cronbach’s α = .92, .89, and .79, respectively) similar to others in Israel (see Shechory-Bitton & Ben David, 2014; Cronbach’s α = .93, .89, and .78, respectively). Each item was ranked on a 4-point Likert-type scale (1 = never , 4 = always ), resulting in a parenting style score based on how often a mother exhibits certain parental behaviors toward her child.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…It includes 62 items divided into 3 scales: authoritative parenting style, authoritarian parenting style, and permissive parenting style. Good internal consistencies were found (Cronbach’s α = .92, .89, and .79, respectively) similar to others in Israel (see Shechory-Bitton & Ben David, 2014; Cronbach’s α = .93, .89, and .78, respectively). Each item was ranked on a 4-point Likert-type scale (1 = never , 4 = always ), resulting in a parenting style score based on how often a mother exhibits certain parental behaviors toward her child.…”
Section: Methodssupporting
confidence: 81%
“…The PSDQ was designed to determine participants' parenting styles (Robinson et al, 1995). The tool was designed to assess Baumrind's (1977Baumrind's ( , 1991 three main parenting typologies (authoritative, authoritarian, and permissive) and has been used in numerous studies (e.g., Johnson, Welk, Saint-Maurice, & Ihmels, 2012;Shechory-Bitton & Ben David, 2014;Slone, Shechner, & Farah, 2011). It includes 62 items divided into 3 scales: authoritative parenting style, authoritarian parenting style, and permissive parenting style.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These legal concepts create avenues, which provide a child with options and choices that can be deemed contrary to sub-Saharan African parenting values. Furthermore, with research showing that children integrate much faster than their parents (Bitton & Ben David, 2014;Wilson & Renzaho, 2015), it is likely that sub-Saharan African migrant families will face further challenges due to intergeneration conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…However, fewer studies address how U.S.-born, adult children of immigrants raise their own children and findings are similarly variable. Bitton and David (2014) found that adult children of immigrants who went from traditional, non-Western societies to a more Western society tended to parent in more authoritative ways and were less tolerant of physical punishment than their parents. However, several studies have also found that foreign-born parents use physical punishment less frequently than U.S.-born parents (Altschul & Lee, 2011;Lee & Altschul, 2015;Taylor et al, 2009).…”
Section: Adult Children Of Immigrantsmentioning
confidence: 99%